2015
DOI: 10.2754/avb201584040373
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary replacement of sunflower oil with milk thistle (Silybum marianum) oil on chicken meat quality and antioxidant status of liver

Abstract: The research focused on the effects of dietary replacement of 3% sunflower oil (SO group) with 3% milk thistle oil (MTO group) on the technological quality of meat, such as pH value, colour (CIE L*, CIE a*, CIE b*), drip loss (%), shear force (N), and cooking loss (%), as well as on the content of fatty acid lipids in broiler breast and thigh muscles. Significant difference (P < 0.05) was determined for pH i, pH u , CIE a*, CIE b* values between groups, although the values for the stated indicators were within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 34 publications
1
9
1
Order By: Relevance
“…On the other hand, Grela et al [21], having introduced 3% or 6% of milk thistle seeds in the diets of fatteners, noted a significant decrease in the share of stearic acid and an increased content of linoleic acid in the longissimus lumborum muscle. The increased share of PUFA in the muscles of birds fed with diets containing Silybum marianum is contrary to the findings of Kralik et al [47] but consistent with those of Grela et al [21] in studies involving fatteners. In addition, the values of atherogenicity index (AI), thrombogenicity index (TI) and hypo-and hypercholesterolemic ratio (h/H) in the breast muscles of chickens receiving experimental feed rations corroborated the tendency noted in the studies by Grela et al [21].…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…On the other hand, Grela et al [21], having introduced 3% or 6% of milk thistle seeds in the diets of fatteners, noted a significant decrease in the share of stearic acid and an increased content of linoleic acid in the longissimus lumborum muscle. The increased share of PUFA in the muscles of birds fed with diets containing Silybum marianum is contrary to the findings of Kralik et al [47] but consistent with those of Grela et al [21] in studies involving fatteners. In addition, the values of atherogenicity index (AI), thrombogenicity index (TI) and hypo-and hypercholesterolemic ratio (h/H) in the breast muscles of chickens receiving experimental feed rations corroborated the tendency noted in the studies by Grela et al [21].…”
Section: Discussionsupporting
confidence: 84%
“…Wierzbowska et al [68] found that the share of polyunsaturated fatty acids (PUFA), including linoleic acid, was lower than in own studies. In turn, Kralik et al [47] noted a higher content (63.11%) of PUFA in milk thistle seeds. Big differences in the share of respective fatty acids in the seeds of Silybum marianum depending on the year of harvest were revealed by Sadowska et al [28].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations